Dendrometer measurements of arctic-alpine dwarf shrubs and micro-environmental drivers of plant growth - Dataset from long-term alpine ecosystem research in central Norway (LTAER-NO) - Löffler, Jörg; Dobbert, Svenja; Pape, Roland; Wundram, Dirk (ERDKUNDE, 2021)
Here, we present fine-scale measurements of stem diameter variation from three common arctic-alpine dwarf-shrub species monitored in two mountain regions of Central Norway. All three species (Betula nana, Empetrum nigrum ssp. hermaphroditum, and Phyllodoce caerulea) are abundant within the studied regions and highly important contributors to potential future arctic-alpine vegetation shifts. A profound understanding of their radial growth patterns therefore has the potential to yield crucial information regarding climate-growth relations within these ecosystems. We used high-resolution dendrometers (type DRO) to monitor 120 specimens, taking measurements near the shoot base of one major horizontal stem. Along with the shrub growth measurements, we measured on-site micro-environmental data at each studied site, including shoot zone and root zone temperatures as well as soil moisture. All data were recorded at an hourly scale and are presented as daily mean values. The monitoring period spanned five full years (2015 - 2019), with additional data from 2014 and 2020. Data were collected within one of the most continental climate regions of Europe, the Vågå/Innlandet region, and in the oceanic climate region Geiranger/Møre og Romsdal, spanning a steep climate gradient over just 100 km horizontal distance. Both study regions are characterized by steep elevational gradients and highly heterogeneous micro-topography. The studied sites were chosen to represent these natural conditions using the transect principle. The collection of our original data is subject of our long-term alpine ecosystem monitoring program since 1991, from which numerous publications function as the basis for a recent project on the use of dendrometer data in alpine ecosystem studies.